Dark diversity framework reconciles Darwin’s naturalization conundrum for freshwater fish invasions - Wen-gang Zhang; Meng Xu; Shu-ya Fan; Jonathan A. Bennett; Ross N. Cuthbert; Jaimie T. A. Dick; Meelis Pärtel; Shao-peng Li (Proceedings of the National Academy of Sciences, 2026)
The spread of invasive species poses a major threat to global biodiversity, yet predicting successful establishment of exotic species in novel environments remains challenging. Darwin’s naturalization conundrum is a longstanding debate over whether exotic species closely or distantly related to native communities are more likely to succeed. Despite its long history, empirical studies continue to yield conflicting evidence. Here, we introduce the dark diversity concept, which refers to species that could theoretically inhabit a site but are currently absent. Combined with observed diversity, dark diversity integrates information on the potential diversity (site-specific species pool size) of the resident community and how completely that pool is locally present (community completeness). Analyzing a 340-y record of successful and failed fish introductions across 516 Swedish lakes, we showed that the effect of phylogenetic relatedness on invasion outcome depends on dark diversity context. Exotics closely related to resident species were more likely to establish in communities with smaller species pools and higher completeness, whereas phylogenetically distant exotic species were more successful in communities with larger species pools and lower completeness. Models with observed species richness obtained considerably less support. Thus, integrating the dark diversity framework clarifies the contrasting effects of phylogenetic relatedness on invasion outcomes, and helps reconcile this 160-y-old conundrum.